A short-term cooling of root-zone temperature increases bioactive compounds in baby leaf Amaranthus tricolor L. - Wittayathanarattana, Takon; Wanichananan, Praderm; Supaibulwatana, Kanyaratt; Goto, Eiji (Frontiers in Plant Science, 2022)
Leafy vegetables that are offered as seedling leaves with petioles are referred to as baby leaf vegetables. One of the most nutritious baby leaves, amaranth (Amaranthus tricolor L.), contains several bioactive compounds and nutrients. Here, we investigated the growth and quality of baby leaf amaranth using a variety of short-term cooling root-zone temperatures (RZT; 5, 10, 15, and 20°C), periods (1, 3, 5, and 7 days), and combinations thereof. We observed that exposing amaranth seedlings to RZT treatments at 5 and 10°C for 1–3 days increased the antioxidant capacity and the concentrations of bioactive compounds, such as betalain, anthocyanin, phenolic, flavonoid, and ascorbic acid; however, extending the treatment period to 7 days decreased them and adversely affected growth. For RZT treatments at 20°C, leaf photosynthetic pigments, bioactive compounds, nutrients, and antioxidant capacity increased gradually as the treatment period was extended to 7 days. The integration of RZTs at 5 and 10°C for one day preceded or followed by an RZT treatment at 20°C for 2 days had varied effects on the growth and quality of amaranth leaves. After one day of RZT treatment at 5°C followed by 2 days of RZT treatment at 20°C, the highest concentrations of bioactive compounds, nutrients, and antioxidant capacity were 1.4–3.0, 1.7, and 1.7 times higher, respectively, than those of the control, and growth was not impaired. The short-term cooling RZT treatments under controlled environments were demonstrated to be adequate conditions for the improvement of target bioactive compounds in amaranth baby leaf without causing leaf abnormality or growth impairment.